Data Storage and Retrieval on Nanoparticles - Kaschel-Carcamo, H; Soto-Gomez, J; Adasme-Soto, P; Casagrande-Denardin, J (IEEE Computer Society, 2017)
Recent advances at developing nanoscale electronic devices lead us to believe that in the near term the nanomemories in the form of nanodisks and nanotubes will replace existing storage systems and will be integrated into the implementation of nanocomputers and complex nanosensor systems. In this work the issue of recording and reading data using the magnetic vortex of nanodisks is addressed. By using the polarity and chirality properties of the magnetic vortex it may be possible to store information in binary or nonbinary form. Nevertheless, as in any storage system, information can be altered by the presence of noise, and therefore it is necessary to incorporate error control coding. In this regard, here we analyse the behaviour of the proposed system using Turbo coding and Low Density Parity Check (LDPC) coding in order to correct errors in the writing and reading process in nanoparticles. Simulations were performed for the binary case considering the polarity of the magnetic vortex to store information. This, because it appears to be the first workable level in the short term, before reaching practical implementations involving the simultaneous control of polarity and chirality to store non-binary data. © 2003-2012 IEEE.